Transient decay of photoinduced current in semiconductors and heterostructures - Scalvi, Luis V. A. [UNESP]; Bueno, Cristina F [UNESP] (IOP Publishing, 2020)
Defects that exhibit some sort of lattice relaxation usually present an energy barrier for electron capture, and the possibility of developing the phenomenon known as persistent photoconductivity (PPC). In this effect, carriers induced in a metastable way remain in a conductive state forever, if the temperature is low enough to avoid the thermally excited retrapping of carriers by large lattice relaxation defects. Although this hypothesis is usually accepted to explain the origin of PPC, there are other principles such as the separation of excited carriers by random local-potential fluctuations. In this paper, we list many sorts of materials that exhibit the PPC effect and the attempts of several researchers to model the transient decay of PPC, seeking parameters in order to understand and model the electrical behavior of these materials. Besides, the PPC effect can be seen as the resulting electrical conduction obtained after removing the electromagnetic irradiation, and it is appealing for applications in a wide range of optoelectronic devices. A personal approach to modeling PPC decay is presented and applied to single crystalline semiconductors, nanocrystalline materials and heterostructures.
Keywords: defect trapping; heterostructure; persistent photoconductivity; semiconductor films